An introduction to the theory of knowledge - Lemos, Noah Marcelino (Cambridge University, 2013)
Providing a clear and accessible introduction to epistemology or the theory of knowledge, this book discusses some of the main theories of justification, including foundationalism, coherentism, reliabilism, and virtue epistemology.